2019
DOI: 10.1111/tbj.13256
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Short‐term Prognostic Value of the 21‐gene recurrence score in African American compared to White American breast cancer patients

Abstract: We evaluated 328 patients (34.8% African American [AA]; 65.2% White American [WA]) with hormone receptor‐positive, HER2/neu‐negative breast cancer. Mean age (60 years); mean tumor size (1.6 and 1.7 cm for AA and WA, respectively) were similar, and mean BMI was higher for AA (33 vs 29.8; P = 0.001). Recurrence score (RS) distribution was similar‐ 8.3% AA and 5.9% WA with high RS (≥31). No significant differences were observed in delivery of chemotherapy stratified by score. With median follow‐up 27.2 months for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In the current clinical practice, 21-gene RS has been used to determine the chemotherapy used in early-stage BC. The findings by Amro et al showed that no significant differences were found in the chemotherapy use after stratification by RS between WA and AA BC [12]. In this study, we found similar chemotherapy use between WA and Chinese BC after stratification by RS.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In the current clinical practice, 21-gene RS has been used to determine the chemotherapy used in early-stage BC. The findings by Amro et al showed that no significant differences were found in the chemotherapy use after stratification by RS between WA and AA BC [12]. In this study, we found similar chemotherapy use between WA and Chinese BC after stratification by RS.…”
Section: Discussionsupporting
confidence: 58%
“…A recent population-based study has shown no significant difference between race and high RS in BC patients aged ≥65 years [16]. The median age of diagnosis was similar between AA and WA BC patients (58-59 years) [12,13], while Chinese patients were much younger (53 years) in our study. We found a similar distribution of RS between WA and Chinese BC.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations